A simple and reversible fluorescent probe based on NBD for rapid detection of hypochlorite and its application for bioimaging1. Issue 97 (21st October 2015) - Shen, Youming; Zhang, Xiangyang; Huang, Xi; Wen, Siyu; Liu, Mingdi; Deng, Yan; Zhang, Youyu; Zhang, Chunxiang; Jin, Junling; Li, Haitao; Yao, Shouzhuo
<x xml:space="preserve">Abstract</x> A simple and reversible fluorescent probe bearing 7-nitrobenz-2-oxa-1, 3-diazole and a selenomorpholine fragment was designed and synthesized.